2017
DOI: 10.1371/journal.pone.0187390
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of CT-guided iodine-125 seed stereotactic brachytherapy and stereotactic body radiation therapy in the treatment of NSCLC

Abstract: This study aimed to assess the dosimetric differences between iodine-125 seed stereotactic brachytherapy (SBT) and stereotactic body radiation therapy (SBRT) in the treatment of non-small cell lung cancer (NSCLC). An SBT plan and an SBRT plan were generated for eleven patients with T1-2 NSCLC. Prescription of the dose and fractionation (fr) for SBRT was 48Gy/4fr. The planning aim for SBT was D90 (dose delivered to 90% of the target volume)≥120Gy. Student’s paired t test was used to compare the dosimetric param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Compared with SBRT, brachytherapy can generate a comparable dose within the planning target volume (PTV D 90 [104.73 ±2.10 Gy vs. 107.64 ±2.29 Gy], mean volume receiving 100% of the prescription dose (V 100% ) [91.65% vs. 92.44%, p = 0.410], while the organs at risk receive only a very low-dose. The mean lung doses (MLD) in brachytherapy were significantly lower than those in SBRT (1.952 ±0.713 vs. 5.618 ±2.009, p < 0.0001) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with SBRT, brachytherapy can generate a comparable dose within the planning target volume (PTV D 90 [104.73 ±2.10 Gy vs. 107.64 ±2.29 Gy], mean volume receiving 100% of the prescription dose (V 100% ) [91.65% vs. 92.44%, p = 0.410], while the organs at risk receive only a very low-dose. The mean lung doses (MLD) in brachytherapy were significantly lower than those in SBRT (1.952 ±0.713 vs. 5.618 ±2.009, p < 0.0001) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have often compared permanent seed brachytherapy to SBRT, with the perception that SBRT would eventually replace brachytherapy; however, it is clear that only brachytherapy can provide the combination of ultimate conformality and minimum normal tissue dose. Seeds might prove worthy opponents to SBRT, with evidence in early lung cancers showing similar target coverage, but a much lower critical organ dose 80 …”
Section: Resultsmentioning
confidence: 99%
“…The higher initial cost of seed brachytherapy, as well as the fact that the technical advancements have lagged behind similar advances in EBRT, require further attention in future studies. Concerns have been raised about the plateau reached in EBRT techniques across different forums, and it might be appropriate to revert to basic radiotherapy, such as seed brachytherapy, to achieve comparable results to SBRT techniques and even proton therapy 80,84 …”
Section: Discussionmentioning
confidence: 99%
“…The ability to implant low energy sources directly into tumors results in a rapid fall-off of dose peripherally, with total sparing of adjacent normal tissues. A study comparing dosimetries of SBRT versus permanent seed brachytherapy for NSCLC showed extremely low-dose to normal tissue with brachytherapy compared with SBRT, but with lower conformity (CI) and heterogeneity (HI) indices in the brachytherapy group [20]; V 100 and D 90 (BED Gy) prescription doses were nearly identical in both treatments (91.6% and 92.4%; 104.7 Gy and 107.6 Gy, respectively), but V 150 was substantially higher with brachytherapy (64.7% and 0%) [20].…”
Section: Discussionmentioning
confidence: 99%